2018
DOI: 10.1111/jep.12921
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapy based on problem‐solving in upper limb function and neuroplasticity in chronic stroke patients: A case series

Abstract: This study indicates that 4 weeks of physiotherapy promoted the recovery of arm function and neuroplasticity in all chronic stroke patients. Future research is recommended to determine the efficacy of this therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 56 publications
0
7
0
8
Order By: Relevance
“…After focal damage, there is a brief, approximately 3 months, window of heightened plasticity, the so-called opportunity window which, in combination with training protocols, leads to large gains in motor function (Zeiler and Krakauer, 2013). Emerging evidence now supports smaller, plastic, and non-compensatory recovery in the chronic stages after a stroke also (Mrachacz-Kersting et al, 2015;Carvalho et al, 2018). To compare the neural biosignals and their utility in robotic gait training after a stroke across studies and to allow the results to be interpreted correctly, it is imperative to report this information.…”
Section: Discussionmentioning
confidence: 99%
“…After focal damage, there is a brief, approximately 3 months, window of heightened plasticity, the so-called opportunity window which, in combination with training protocols, leads to large gains in motor function (Zeiler and Krakauer, 2013). Emerging evidence now supports smaller, plastic, and non-compensatory recovery in the chronic stages after a stroke also (Mrachacz-Kersting et al, 2015;Carvalho et al, 2018). To compare the neural biosignals and their utility in robotic gait training after a stroke across studies and to allow the results to be interpreted correctly, it is imperative to report this information.…”
Section: Discussionmentioning
confidence: 99%
“…The Bobath concept used in the present study addressed the integration of postural control and task performance. In addition, the integration of sensory information in motor control and perception could be promoted at the cortical level through specialised handling, supporting surface, and gravity (Bobath, 1978;Vaughan-Graham and Cott, 2016;Carvalho et al, 2018). The combination of stability and mobility organised postural control of the multijoint kinetic chain of the trunk and limbs (Hodges et al, 2002;Gjelsvik, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, this may not be the case for those with severe deficits (Abdullahi, 2018). In a recent study, in case of severe deficit, upper limb function was found to improve after 20 sessions of the Bobath intervention over 4 weeks (Carvalho et al, 2018). Most items in the Wolf Motor Function Test demonstrated improvement in both movement time and functional ability after the 6-week Bobath therapy programme.…”
Section: Original Research © 2019 the Authorsmentioning
confidence: 97%
See 2 more Smart Citations